Enthusiast! Essays on Modern American Literature - Herd, David (Manchester University Press, 2007)
This book takes enthusiasm to be a defining feature of American literature, showing how successive major writers - Melville, Thoreau, Pound, Moore, Frank O'Hara and James Schuyler - have modernized and re-modeled Emerson's founding sense of enthusiasm. The book presents the writer as enthusiast, showing how enthusiasm is fundamental to the composition and the circulation of literature. Enthusiasm, it is argued, is the way literary value is passed on.Starting with a brief history of enthusiasm from Plato to Kant and Emerson, the book features chapters on each of Melville, Thoreau, Pound, Moore, O'Hara, and Schuyler. Each chapter presents an aspect of the writer as enthusiast, the book as a whole charting the changing sense of literary enthusiasm from Romanticism to the present day. Lucidly written and combatively argued, the book will appeal to readers of American Literature or Modern Poetry, and to all those interested in the circulation of literary work.